Os tipos literários na prosa de Lima Barreto - Ramos, Carolina Moura Barroso (2015)
This study aims at identifying and interpreting the variety of literary types found in Lima Barreto s prose. We understand the typification process in the building of a character is related to two diffferent and articulated sources, in one side there is the living world, from which it can be taken; in the other side, there are the literary traditions, in which the types go round and tranform themselves, getting new contents. Nonetheless, the perspective of this study is to analyze the typesin the literary universe of a unique author that, as far as we know, built a critical vision of the brazilian society in the chaotic age of republican transition, in the beginning of the 20th century. We start from the idea that in the literary picturing of a realistic character the typification of characters and the narrative situations repeats itself and doesn t depend on a flat or round nature. Therefore, the literary typeis not seen as a superficial simplification, but as a try to elaborate a previous notion, an almost concept, which has the role to elucidate the historical and social situations represented in the narratives. We understand that the critical content of Lima Barreto s literature can be considered consistent and a work of quality due to the typification. And this is one of the reasons for his critical fortune that got him a place as a Brazilian 20th century literature canone. From the methodological point of view, this study is far from the perspective of bringing up the typical characters in a substantial way and chooses to analyze them in their articulations during the narrative process; so the type doesn t exist alone, but as the result of intercrossed relationships in which they are in: the bovarist and quixotic characters that are in Lima Barreto s literature, show up in a contradictory game against the conformist characters, the smart, the naive, the positivist, the skeptic that surround them. In this way, we try to situate ourselves in the inner narratives perspective, eventhough, in order to to do so we have searched for the reality of the living world in Rio de Janeiro and the belle époque biographical, historical and sociology s elements to understand the analyzed narratives picturing. In Lima Barreto s literature s corpus we analyse four short stories ( Na janela , Miss Edith e seu tio , O filho da Gabriela , O homem que sabia javanês ) and the novel O triste fim de Policarpo Quaresma ; but, in order to do so, we have gone through his chronicles as in his other works of fiction, elements that allow na intercrossed analysis of Lima Barreto s typicological universe